New insights into urine-based assessment of polycyclic aromatic hydrocarbon-exposure from a rat model: Identification of relevant metabolites and influence of elimination kinetics. (September 2017) - Grova, N.; Faÿs, F.; Hardy, E.M.; Appenzeller, B.M.R.
Abstract: A gas chromatography tandem mass-spectrometry method dedicated to the analysis of 50 metabolites of polycyclic aromatic hydrocarbons (OH-PAHs) was applied to urine specimens collected from female Long Evans rats under controlled exposure to a mixture of PAHs (at 7 doses ranging from 0.01 to 0.8 mg/kg, by gavage, 3 times per week for 90 days). On four occasions (day 1, 28, 60 and 90), urine samples were collected over a 24 h period. Among these 50 OH-PAHs, 41 were detected in urine samples. Seven additional OH-PAHs were identified for the first time: 1 corresponding to metabolite of pyrene and 3 of anthracene. Strong linear dose versus urinary concentration relationships were observed for 25 of the 41 OH-PAHs detected in rat urine, confirming their suitability for assessing exposure to their respective parent compound. In addition, some isomers (e.g. 1-OH-pyrene, 3-OH-/4-OH-chrysene, 10-OH-benz[ a ]anthracene, 8-OH-benzo[k]fluoranthene, 11-OH-benzo[ b ]fluoranthene and 3-OH-benzo[ a ]pyrene) that were detected starting from the lowest levels of exposure or even in controls were considered particularly relevant biomarkers compared to metabolites only detected at higher levels of exposure. Finally, on the basis of the excretion profiles (on days 1, 28, 60 and 90) and urinary elimination kinetics of each OH-PAH detected at days 1 and 60, this study highlighted the fact that sampling time may influence the measurement of metabolites in urine. Taken together, these results provide interesting information on the suitability of the analysis of OH-PAHs in urine for the assessment of PAH exposure, which could be taken into consideration for the design of epidemiological studies in the future. Graphical abstract: Highlights: Selection of new accurate 4 to 5-ring OH-PAHs for the assessment of PAH exposure. Identification of new OH-PAHs in urine. Linear relationships between dose and urinary concentration for 25 OH-PAHs in urine. Influence of exposure duration on urine analysis for PAH exposure assessment. Influence of elimination kinetic on urine analysis for PAH exposure assessment. Abstract : This study focuses on the identification of relevant monohydroxylated metabolites in urine and the influence of their elimination kinetics in rat for the assessment of PAH exposure.